Sistem Informasi Geografis Peta Lokasi Toko Oleh-oleh Khas Wonosari Berbasis Website - Maria Atik Sunarti Ekowati; Sri Wening; Kristyana Dananti; Darsini Darsini (JITU : Journal Informatic Technology And Communication, 2023)
Wonosasri, Gunung Kidul district, Special Region of Yogyakarta is famous for having quite a lot of interesting tourist destinations for tourists to visit. Tourist attractions that are quite famous in Indonesia are Wediombo Beach, Nglambor Beach, Becici Hill Pine Forest, Oya River, Ngringrong Valley, Sri Gethuk Waterfall, Ki Ageng Giring III Grave, Baron Beach, Wunung Giri Sela Kandha, Stone Garden, Kejawan Temple, Tanding Cave, Pindul Cave, Kalisuci Cave Tubing, Jomblang Cave, HeHa Sky View, Gesing Beach, Sadranan Beach, Drini Beach, Bukit Bintang, Puncak Segoro, Tanding Cave, Embung Glangeran, Slili Beach and many others. Apart from being famous as an attractive tourist destination, Wonosari Yogyakarta also has various types of souvenirs typical of Tiwul food, Gatot, Nasi Tiwul, Prawn Peyek, Fried Grasshoppers, Fried Lungkrung, Cassava Crackers, Various processed sea fish, Seaweed Peyek, Manggleng, Pathilo , and ornamental stone handicrafts, wooden and wooden batik crafts, natural colored batik crafts, bamboo crafts, vetiver crafts, natural handicrafts, silver crafts, cast metal crafts, blacksmith crafts, copper and brass crafts, and so on. Tourists who want to buy souvenirs often have difficulty finding souvenir shop locations. This research aims to develop a system that can provide information on the location of souvenir shops around users. This research was built using the waterfall method starting with the analysis, design, implementation and stages testing. The programming language used is PHP and MySql for the database. The result of this research is that a website that can display locations can display the distance and information on souvenir shops so that it really helps tourists/people to see the distance and information on souvenir shops. According to the UAT testing carried out, it is hoped that 90% of tourists/people will be helped. with the development of this system.